EFEKTIVITAS PEMBERIAN TABLET TAMBAH DARAH DAN VITAMIN C TERHADAP KADAR HEMOGLOBIN IBU HAMIL DI WILAYAH KERJA UPT BLUD PUSKESMAS MENINTING - Dwi Zulqaidah, Annisa; Iin Rumintang, Baiq (MEDIA ILMU KESEHATAN, 2019)
Background:Based on the results of Basic Health Research in 2013, the prevalence of anemia in pregnant women in Indonesia 37.1%. Prevalence of anemia in pregnant women in the working area of ​​UPT BLUD Meninting Health Center in 2017 amounted to 28.18 %. To increase the absorption of hemoglobin levels, iron supplementation needs to be combined with other micronutrients such as vitamin C Objective:To know the effectiveness of giving tablets added blood and vitamin C to the hemoglobin level of pregnant women Method:This research used Quasi Experiment with Non Equivalent Control Group design with 30 samples divided into intervention and control group Results:The characteristics of pregnant women found that most of them were 20-35 years old (83,3%), high school education (56,7%), respondents who did not work or housewives (96,7%), respondents multiparas (70%), the distance of pregnancy >5 years (61,9%). The average hemoglobin levels of pregnant women who only get tablets added blood 0.36 gr/dL. The average hemoglobin levels of pregnant women who get tablets added blood and vitamin C amounted to 1.2 gr/dL. Statistical test results independent t test obtained p value of 0.006 Conclusion:There is effectiveness of giving tablets added blood and vitamin C to pregnant woman's hemoglobin level